2013
DOI: 10.1016/j.bmc.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Dieckol, a SARS-CoV 3CLpro inhibitor, isolated from the edible brown algae Ecklonia cava

Abstract: SARS-CoV 3CL(pro) plays an important role in viral replication. In this study, we performed a biological evaluation on nine phlorotannins isolated from the edible brown algae Ecklonia cava. The nine isolated phlorotannins (1-9), except phloroglucinol (1), possessed SARS-CoV 3CL(pro) inhibitory activities in a dose-dependently and competitive manner. Of these phlorotannins (1-9), two eckol groups with a diphenyl ether linked dieckol (8) showed the most potent SARS-CoV 3CL(pro) trans/cis-cleavage inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 31 publications
4
106
0
2
Order By: Relevance
“…Noteworthy, dieckol (11) has already reported as one of the most potent SARS-CoV-1 M pr phlorotannin inhibitors (IC50 = 2.7 μM). Docking studies highlighted that interactions between dieckol and the amino acid residues in the active site of M pr are mainly constituted by a H-bonds network with a calculated binding energy of −11.76 kcal/mol [26], that is comparable to the energy found by us with the SARS-CoV-2 M pr .…”
Section: $$supporting
confidence: 69%
“…Noteworthy, dieckol (11) has already reported as one of the most potent SARS-CoV-1 M pr phlorotannin inhibitors (IC50 = 2.7 μM). Docking studies highlighted that interactions between dieckol and the amino acid residues in the active site of M pr are mainly constituted by a H-bonds network with a calculated binding energy of −11.76 kcal/mol [26], that is comparable to the energy found by us with the SARS-CoV-2 M pr .…”
Section: $$supporting
confidence: 69%
“…Hwang et al. reported a suppressive effect of dieckol on UVB‐induced skin cancer . Interestingly, a recent study showed an inhibitory effect of diekcol on adipogenesis of 3T3‐L1 via AMPKα activation .…”
Section: Discussionmentioning
confidence: 99%
“…Dieckol is known to be a major phlorotannin of both Seapolynoland Ecklonia cava itself . Various biological studies of dieckol to date have been reported . Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Through in silico and biological processing, a series of small molecules, including those from natural compounds, have been screened and confirmed to directly inhibit these important proteins in SARS or Middle East respiratory syndrome (MERS) coronavirus [17][18][19][20][21][22][23]. The gene sequence of 2019-nCoV has been released, which suggests high similarities between the main proteins in this virus and those previously identified in SARS-Cov or MERS-Cov [24,25].…”
Section: Introductionmentioning
confidence: 94%